PENGARUH LATIHAN DRIBBLING BOLAK-BALIK DAN DRIBBLING ZIG-ZAG TERHADAP PENINGKATAN KECEPATAN DRIBBLE AKADEMI FUTSAL TOKO KECIL KUNINGAN - Fiqhan Ilman Nirwana (Journal of Physical Education and Sport Science, 2022)
Fiqhan Ilman Nirwana (NIM 182223053) (2021) with the title "The effect of back and forth dribbling and zigzag training on increasing dribbling speed in the Toko Kecil Kuningan futsal academy futsal game". This study aims to determine the effect of back and forth dribbling and zigzag training on increasing the dribbling speed of futsal players at Toko Kecil Kuningan futsal academy. The method used in this research is the experimental method. The research design used was a two group pretest-posttest design. Sampling using random sampling technique with a sample of 30 people. The research instrument is the Illinois agility run test. The data analysis techniques in this study were normality test, homogeneity test and hypothesis testing which were used to determine the effect of back and forth dribbling and zig-zag dribbling on increasing dribbling speed in the futsal game of Toko Kecil Kuningan futsal academy. From the results of statistical testing in groups 1 and 2 with a value of 0.000 less than 0.05. The test conducted by SPSS 21.0 for windows shows that the data is normally distributed, with homogeneous variance, so the hypothesis is accepted, meaning that there is an effect of back and forth dribbling and zig-zag dribbling exercises on increasing dribbling speed in the futsal game of the Toko Kecil Kuningan academy. The conclusion in this study is that there is an effect of back and forth dribbling and zig-zag dribbling exercises to increase dribbling speed in the futsal game of Toko Kecil Kuningan futsal academy.